Effects of water temperature, dissolved oxygen and total suspended solids on juvenile barbonymus schwanenfeldii (Bleeker, 1854) and Oreochromis Niloticus (Linnaeus, 1758) - Nyanti, Lee; Soo, Chen Lin; Ahmad-Tarmizi, Nona Nabilah; Abu-Rashid, Nik Nurul Kamila; Ling, Teck Yee; Sim, Siong Fong; Grinang, Jongkar; Ganyai, Tonny Anak; Lee, Karen Suan Ping (BIOFLUX, 2018)
The aim of the present study was to investigate the effects of water temperature, dissolved oxygen (DO), and total suspended solids (TSS) in water on an indigenous fish species, Barbonymus schwanenfeldii (Bleeker, 1854), and an exotic fish species, Oreochromis niloticus (Linnaeus, 1758) in Malaysia. The survival rate, growth performance, and feed conversion ratio (FCR) of juvenile fish were tested in different water quality conditions for 30 days. The water temperature of 30°C, DO value of less than 4 mg L-1, and TSS content of 1000 mg L-1 are believed to be harmful to fish life. The result indicates that the O. niloticus juveniles are relatively tolerant of high water temperature and TSS in term of survivorship, whereas the B. schwanenfeldii juveniles are more vulnerable to the two parameters. Reduced DO value had influenced the survival rate of both fish species in a similar way where 100% mortality of both fish species occurred at DO value less than 2 mg L-1. The growth performance of juvenile B. schwanenfeldii was less susceptible to the changes of water temperature and DO whereas the growth performance of juvenile O. niloticus was influenced by the two parameters. The results show that the FCR of both fish increased with high water temperature and TSS. The juvenile B. schwanenfeldii was able to sustain its growth by consuming additional food in high water temperature. Increased DO value significantly improved the FCR of O. niloticus juvenile but not of B. schwanenfeldii juvenile. © 2018, BIOFLUX SRL. All Rights Reserved.